Challenges to Epidemiologic Study of Rheumatic Disorders in the Developing Countries - Haq, Syed Atiqul; Islam, Mohammad Saiful; Naheed, Aliya (Bangladesh Journal of Medicine, 2013)
Bangladesh Journal of Medicine, Vol 24 No 1, 2013, Page 1-3 DOI: http://dx.doi.org/10.3329/bjmed.v24i1.15026